2008
DOI: 10.1007/s00127-008-0412-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for depression in truck drivers

Abstract: Truck drivers are at increased risk for depression when compared to the general population. Efforts to increase awareness of this problem and to limit the use of stimulants, as well as measures to improve job satisfaction, particularly among the wage-earning drivers, may have a positive impact on mental health in these workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 35 publications
2
43
1
5
Order By: Relevance
“…This is a subject that needs further clarification. Prospective studies could test the effects of antidepressants in daytime somnolence, cognitive function, reduced alertness, and driving ability (29). We confirm that poor sleep quality affects more than half of diabetic patients (16).…”
Section: Discussionsupporting
confidence: 58%
“…This is a subject that needs further clarification. Prospective studies could test the effects of antidepressants in daytime somnolence, cognitive function, reduced alertness, and driving ability (29). We confirm that poor sleep quality affects more than half of diabetic patients (16).…”
Section: Discussionsupporting
confidence: 58%
“…In the study carried out by Teles et al, 19 the prevalence of amphetamine use was of 30%. In the work of Silva-Júnior et al, 13 35% of the interviewees reported using stimulants, of whom 90.6% reported consumption of these substances by their colleagues. In these three studies, the prevalence that was found is higher than in the present research.…”
Section: Discussionmentioning
confidence: 98%
“…Penteado et al 12 identifi ed a prevalence of 43% of alcohol use in the Northeast of Brazil. In the study conducted by Silva-Júnior et al, 13 carried out in the city of Fortaleza (Northeastern Brazil), 48.3% of the interviewees reported consuming alcohol during workdays and 88.6% reported that their colleagues maintained this practice. Ferreira et al 4 showed that 41.9% of the truck drivers who traveled along routes in the interior of the State of São Paulo reported using alcohol in the seven days that preceded the research.…”
Section: Discussionmentioning
confidence: 99%
“…Em termos ocupacionais, os participantes tinham larga experiência como motoristas profissionais, com excessiva carga diária de trabalho, percorrendo longas distâncias. Esses dados são consistentes com os de estudos prévios, particularmente no que diz respeito a idade 23,24,25 , estado civil 23,25 , anos de experiên-cia 26,27 , carga diária de trabalho 26,28,29,30 e turno de trabalho 26 .…”
Section: Discussionunclassified